Neuroprotective Effect and Molecular Mechanism of [6]-Gingerol against Scopolamine-Induced Amnesia in C57BL/6 Mice. (31st January 2018) - Kim, Chang-Yul; Seo, Yongtaek; Lee, Chan; Park, Gyu Hwan; Jang, Jung-Hee
Abstract : We have investigated the neuroprotective and memory enhancing effect of [6]-gingerol (GIN), a pungent ingredient of ginger, using an animal model of amnesia. To determine the neuroprotective effect of GIN on cognitive dysfunction, scopolamine (SCO, 1 mg/kg, i.p.) was injected into C57BL/6 mice, and a series of behavioral tests were conducted. SCO-induced behavior changes and memory impairments, such as decreased alteration (%) in Y-maze test, increased mean escape latency in water maze test, diminished step-through latency in passive avoidance test, and shortened freezing time in fear condition test, were significantly prevented and restored by the oral administration of GIN (10 or 25 mg/kg/day). To further verify the neuroprotective mechanism of GIN, we have focused on the brain-derived neurotrophic factor (BDNF). The administration of GIN elevated the protein expression of BDNF, which was mediated via the activation of protein kinase B/Akt- and cAMP-response element binding protein (CREB) signaling pathway. These results suggest that GIN may have preventive and/or therapeutic potentials in the management of memory deficit and cognitive impairment in mice with amnesia.